2016
DOI: 10.3847/0004-637x/831/1/69
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Far-Infrared Co Emission From Protostars

Abstract: We investigate the evolution of far-IR CO emission from protostars observed with Herschel/PACS for 50 sources from the combined sample of HOPS and DIGIT Herschel key programs. From the uniformly sampled spectral energy distributions, whose peaks are well sampled, we computed the L bol , T bol ,and L L bol smm for these sources to search for correlations between far-IR CO emission and protostellar properties. We find a strong and tight correlation between far-IR CO luminosity (L CO fir ) and the bolometric lum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 90 publications
4
30
0
Order By: Relevance
“…We found a strong linear relation between L CO and L bol , which can be expressed as log(L CO ) = (0.62 ± 0.14)log(L bol ) − 2.10 ± 0.13, (5) but no systematic offset of L CO distinguished by the T bol of the sources. The same scenario is also found for the HOPS and DIGIT programs (Manoj et al 2013(Manoj et al , 2016. We found that the classification of embedded protostars still remains uncertain with the addition of Herschel -SPIRE spectra.…”
Section: Sed Classificationsupporting
confidence: 80%
“…We found a strong linear relation between L CO and L bol , which can be expressed as log(L CO ) = (0.62 ± 0.14)log(L bol ) − 2.10 ± 0.13, (5) but no systematic offset of L CO distinguished by the T bol of the sources. The same scenario is also found for the HOPS and DIGIT programs (Manoj et al 2013(Manoj et al , 2016. We found that the classification of embedded protostars still remains uncertain with the addition of Herschel -SPIRE spectra.…”
Section: Sed Classificationsupporting
confidence: 80%
“…The lack of an obvious outflow from HOPS-108 has implications for the interpretation of its far-infrared CO emission. HOPS-108 is among the strongest far-infrared CO emitters, significantly above the relationship found by Manoj et al (2016). Thus, HOPS-108 may not actually be responsible for generating the CO emission and instead it is dominated by the terminal shock from the nearby HOPS-370 outflow as suggested by González-García et al (2016b).…”
Section: Remaining Questionsmentioning
confidence: 81%
“…Karska et al (2018) and Galametz et al (2019) for IRAS4A. Chini et al (1997) and Manoj et al (2016) for OMC3 MMS6. (b) Internal luminosity.…”
Section: Discussionmentioning
confidence: 99%